FILANTROPI UNTUK KEADILAN SOSIAL SEBUAH STUDI PENDAHULUAN TENTANG POTENSI DAN POLA DERMA PADA MASYARAKAT MINANGKABAU DAN KEMUNGKINAN PENGEMBANGANNYA UNTUK KEADILAN SOSIAL - Yulkardi ,; Yunarti . (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2014)
In one of paragraph of an academic document of the National Social Welfare System revealed that the economic development of Indonesia in the past suffered serious distortion, so that growth is not necessarily improve welfare. Distorted development had led to serious social problems such as poverty, family disharmony, violence, economic vulnerability, injustice against women, and rising unemployment. Social problems can give birth de-humanization and weakening values and human relationships. Furthermore, all these social problems hasbecome a major obstacle for economic and social development